First case of 18F-choline uptake in acoustic schwannoma after stereotactic radiotherapy - Arico, Demetrio; Giardina, Claudio; Tuscano, Carmelo; Picone, Antonio; Militano, Vincenzo (World Journal of Nuclear Medicine, 2019)
A 69-year-old male patient, with bilateral hypoacusia and tinnitus, had a diagnosis of left vestibular schwannoma with synchronous meningioma on the left frontal lobe. After partial surgical resection of the acoustic schwannoma, this was followed by stereotactic radiosurgery on the residual lesion. The patient had a metachronous prostate cancer treated with conformal radiotherapy associated to 6 months of hormone therapy with luteinizing hormone/releasing hormone analog. During follow-up, prostate-specific antigen value increased to 0.27 ng/mL and the patient underwent 18F-methylcholine positron emission tomography/computed tomography (18F-choline PET/CT). The whole-body scan demonstrated a focus of increased uptake at level of the left cerebellopontine angle and at the left frontal lobe, corresponding to the known vestibular schwannoma and meningioma. A subsequent brain contrast-enhanced magnetic resonance imaging (MRI) showed an increased dimension of the left cerebellopontine neuroma and dimensional stability of the left frontal meningioma compared with previous MRI of 6 months earlier. To the best of our knowledge, we describe the first case of a 18F-choline PET/CT demonstrating a relapse of a vestibular schwannoma after stereotactic radiotherapy.
Keywords: 18F-Choline; positron emission tomography/computed tomography; schwannoma